THE CHALLENGES OF THE NEW COOPERATIVE LEGAL FRAMEWORK IN MADAGASCAR - Tadjudje, Willy (International Journal of Cooperative Law, 2024)
The cooperative legal framework is changing in Madagascar. A new cooperative law has been in force since August 2023, and its implementing decree is currently being drawn up. The aim of this contribution is to outline the limitations of the former law, as well as the reforms introduced by the new law. This post is very general and will soon be supplemented by a detailed paper on the new Malagasy cooperative legal framework, once the decree implementing the new Malagasy cooperative law comes into force.